The degree of transformational leadership practice in the Ministry of Education in the Sultanate of Oman and its impact on employees’ organizational commitment - Alawaid, Salim Issa Mahad; Al-Hidabi, Dawood Abdulmalek; Aldaba, AbdulMajid Mohammed AbdulWahhab (Journal of Educational and Psychological Sciences, 2022)
This study aimed to identify the degree of implementing the transformational leadership in the Ministry of Education in the Sultanate of Oman, and its impact on the employee’s organizational commitment. To achieve the objectives of the study, the quantitative approach was used, and a questionnaire of (24) items was developed to measure the study’s variables. After verifying the validity and reliability of the tool, it was distributed to a sample of (404) employees in the Ministry of Education and its directorates in some Omani Governorates. The study data was analyses in two stages: the first stage was done using the SPSS program to conduct a descriptive analysis of the study sample, and to measure the degree of implementing transformational leadership and the level of organizational commitment. The second stage was done by using AMOS program to perform the confirmatory factor analysis (CFA) of the overall measurement model of the study, and the structural model test to examine the direct relationship between transformational leadership and organizational commitment. The results of the study revealed that the implementing of transformational leadership in all its dimensions in the Ministry of Education was high, the mean was (3.96), and that the level of organizational commitment among employees was medium, the mean was (3.67). The study revealed a positive and significant impact of the implementing transformational leadership on the organizational commitment. The study included some conclusions and some recommendations such as enhancing the awareness of the importance of adopting a transformational leadership style, and implementing training courses to develop the capabilities of the leadership of administrative units, and preparing them to apply the transformational leadership style. In addition the study include some suggestions for future studies.